Supporting LGBT Lives? Complicating the suicide consensus in LGBT mental health research. (February 2017) - Bryan, Audrey; Mayock, Paula
This article locates itself within an emergent, counter-discursive body of scholarship that is critical of universalizing depictions portraying queer-identified or LGBT youth as vulnerable and 'at-risk' of a range of negative mental health outcomes, including self-harm and suicidality. Drawing on key findings from a large-scale, mixed-methods study exploring the mental health and well-being of LGBT people, we seek to contribute to the development of a more expansive understanding of LGBT lives by demonstrating the diverse ways people engage with their sexuality and gender identity and illuminating the complex meanings that those LGBT people who have experienced psychological and suicidal distress ascribe to their feelings, thoughts and actions.